House of Dance and Feathers (Oz, 2006)
An article about a group of K-State architecture students led by professors Patrick Rhodes and Larry Bowne who traveled to New Orleans to construct a house for Ronald Lewis and Mardi Gras Indian who maintained a private museum in his back yard known as the House of Dance and Feathers.